Persepsi Siswa terhadap Pembelajaran Matematika dan Kaitannya dengan Minat Serta Sikap Belajar Siswa - Ade Ayu Dwiguningtyas; Denik Agustito; Betty Kusumaningrum; Krida Singgih Kuncoro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to describe the perceptions of class X students of Light Vehicle Engineering (TKR) towards mathematics learning and its impact on students' learning interests and attitudes. The study was conducted at one of the vocational schools in Yogyakarta with a qualitative approach and descriptive method. Data were collected using triangulation techniques through observation, open questionnaires, and in-depth interviews. The results showed that most students had negative perceptions of mathematics, which were considered difficult, confusing, and irrelevant to life or work in the automotive field. This perception resulted in low interest and negative attitudes such as indifference, passivity, and lack of enthusiasm. However, there were students who showed positive attitudes when the material presented was considered relevant and easy to understand. These findings indicate a close relationship between students' perceptions, interests, and attitudes towards mathematics learning. Therefore, it is important for educators to design learning strategies that are more contextual, applicable, and in accordance with the world of work in order to form positive perceptions of mathematics.